2021
DOI: 10.1029/2020jf005872
|View full text |Cite
|
Sign up to set email alerts
|

Calving at Ryder Glacier, Northern Greenland

Abstract: The Greenland ice sheet has had an increasingly negative mass balance during recent decades (Mouginot et al., 2019), and has been responsible for ∼0.76 ± 0.1 mm/yr of global sea level rise (SLR) between 2005(Cazenave et al., 2018. Greenland was the most important cryospheric contributor to SLR during this period, above Mountain glaciers (0.74 ± 0.1 mm/yr) and Antarctica (0.42 ± 0.1 mm/yr) (Cazenave et al., 2018). Mass losses in Greenland are driven by climatic and oceanographic warming (Christoffersen et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Secondly, nondrainage dominated years are characterized by a slow but steady increase in total lake area over the melt season. Our analysis identifies 2018 as such a year (Figure 7), also observed by Holmes et al (2021), and a similar evolution of total lake area was shown by Sundal et al (2009) for years 2006 and 2007 and supported by imagery analysed here for these years (Figure 6). Overall, lake area evolution over the melt season can therefore be seen as an indicator for identifying whether meltwater drainage or storage was the dominant process during a particular year.…”
Section: Inter-annual Variability In Lake Drainage Behaviorsupporting
confidence: 87%
See 4 more Smart Citations
“…Secondly, nondrainage dominated years are characterized by a slow but steady increase in total lake area over the melt season. Our analysis identifies 2018 as such a year (Figure 7), also observed by Holmes et al (2021), and a similar evolution of total lake area was shown by Sundal et al (2009) for years 2006 and 2007 and supported by imagery analysed here for these years (Figure 6). Overall, lake area evolution over the melt season can therefore be seen as an indicator for identifying whether meltwater drainage or storage was the dominant process during a particular year.…”
Section: Inter-annual Variability In Lake Drainage Behaviorsupporting
confidence: 87%
“…Seaward of its grounding line, Ryder Glacier features a floating ice tongue c. 25 km long and c. 10 km wide (Hill et al, 2017;Wilson et al, 2017;Holmes et al, 2021). Episodically, calving takes place from this tongue (Wilson et al, 2017), with calving styles described in detail in Holmes et al (2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations